Cognitive space “hospitality” in the Karakalpak, Russian and English languages (Journal of Universal Science Research, 2023)
Concepts have a pronounced structure due to the fact that they are formed at the level of consciousness, and their content is information about the objects of the world, obtained by a person in the process of cognitive activities. The concept of "hospitality" can be considered universal, universal, but practical material shows that different in languages is the structure of cognitive models representing this concept. Each concept expressed by verbal means has its own own semantic form determined by its values, which is characterized by ethnocultural conditioning, since in it expresses all connotative, modal, emotional, expressive, pragmatic and other assessments. Hence it follows that the analysis of each concept is individual, since individual and its specific history. The concept of "hospitality" is a multifaceted structure. How any unit of the cognitive base of the concept under study has a certain set of associations, structure of cognitive space "hospitality" we propose to consider from the point of view the point of view of its national and cultural marking, which will allow it is better to present the images and associations associated with the concept in English, Russian and Karakalpak languages.